Osoba nauczyciela wobec patologii w przestrzeni edukacyjnej - Ptak , Małgorzata M.; Śmiałek , Mirosław J. (Studia Edukacyjne, 2020)
In modern education, a personal attitude towards a teacher defines their mission in education. Equally important is an understanding of one’s subjectivity as a human being and the importance of others in life-long learning, more widely perceived as the growth of humanity. The role of teachers and their educational mission are faced with a number of dynamic dysfunctions, which effectively challenge their ability of achieving teaching career goals, especially through the prism of leadership within education.